2005
DOI: 10.1002/ana.20580
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological properties of human hypothalamic hamartomas

Abstract: The hypothalamic hamartoma (HH) is a rare developmental malformation often characterized by gelastic seizures, which are usually refractory to medical therapy. The mechanisms of epileptogenesis operative in this subcortical lesion are unknown. In this study, we used standard patch-clamp electrophysiological techniques combined with histochemical approaches to study individual cells from human HH tissue immediately after surgical resection. More than 90% of dissociated HH cells were small (6-9 microm soma) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 51 publications
5
97
0
1
Order By: Relevance
“…4,9,11,12,16,21,22,26,35,45 The epileptogenic activity of HHs has been recently demonstrated at the cellular level: detailed electrophysiological analysis of slices taken from surgical specimens showed the predominance of small GABAergic inhibitory neurons exhibiting an intrinsic "pacemaker-like" behavior. 54 The concept that surgical intervention should mainly target the HH was not easy to accept. The path toward acceptance was paved by failed procedures such as temporal or frontal lobectomies, parietal corticectomies, or corpus callosotomies.…”
Section: Pathophysiology: Intrinsic Epileptogenesis Of Hhsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,9,11,12,16,21,22,26,35,45 The epileptogenic activity of HHs has been recently demonstrated at the cellular level: detailed electrophysiological analysis of slices taken from surgical specimens showed the predominance of small GABAergic inhibitory neurons exhibiting an intrinsic "pacemaker-like" behavior. 54 The concept that surgical intervention should mainly target the HH was not easy to accept. The path toward acceptance was paved by failed procedures such as temporal or frontal lobectomies, parietal corticectomies, or corpus callosotomies.…”
Section: Pathophysiology: Intrinsic Epileptogenesis Of Hhsmentioning
confidence: 99%
“…Electrophysiological characterization of HH neurons has shown that an intrinsic epileptogenic activity is present. 4,5,21,22,32,54 Epileptogenic HH are invariably attached to one or both of the mammillary bodies. 15 Spread of the epileptogenic activity and induction of generalized seizures require access to the thalamocortical loops via the mammillothalamic tract.…”
mentioning
confidence: 99%
“…31,32,47 Lastly, pacemaker-like activity can be found within clusters of cells in resected hamartomas, supporting the notion that epileptic properties are indeed intrinsic to the hamartomas themselves. 60 …”
Section: Electroencephalography Studiesmentioning
confidence: 99%
“…41,64 In addition to a continuous pacemaker-like firing pattern, these small neurons, which express GABA A receptors and are probably inhibitory interneurons, also exhibit irregular spiking and bursting firing patterns. 118 In contrast, spontaneous activity was not detected in large HH neurons. 41 Ultrastructural studies have also demonstrated that these 2 neuronal populations have distinct morphological and synaptic profiles.…”
mentioning
confidence: 93%